Psycho-semantic representation of a collective subject of volunteer activity in the structure of subjective experience - Koval, Hennadiy (Psychological Prospects Journal, 2022)
Purpose. The article is devoted to the theoretical and empirical substantiation of the conceptual foundations of the study of the «criterion» as a specific psychic formation within the context of the development of the issue of variability of socio-psychological forms of psyche.Method.The research was implemented by filling out an individual volunteer questionnaire. In particular, in order to achieve the purpose and fulfil the tasks of the study, the data, obtained by the results of the following questionnaires, have been used: Semantic differential» by C. Osgood; «Life-meaning orientations test» (LMO) by D. Leontief; «Interpersonal reactivity index» by M. Davis, adapted by T. Koriahina, N. Kuhtova et all; «Portrait Values Questionnaire» (PVQ) by S. Schwartz, adapted by I. Semkiv; Modified Ingleghart Values Questionnaire by Khabibulin and Deineka. The sample of the research consisted of 302 volunteers aged 17 to 80 years from more than 15 cities of Ukraine.Results. The presence of the specifics conditioning the interconnection between different subject areas of assessment was shown. In particular, the specific of the interconnection between the assessment of the meaningfulness of volunteer activity and the assessment of the significance of a certain value-motivational tendency was found out. Namely, there is a core of interconnection, which is demonstrably concentrated in the high density of positive correlation of «meaningfulness» scales with the values of «Self-Direction» and «Stimulation» and a gradual decline in density relative to other value-motivational tendencies. At the same time, the interconnection between the assessment of the significance of the value-motivational tendency and the psycho-semantic assessment of the image of the volunteer community is characterized by a polar opposition. Namely, the opposition in the distribution of indicators of psycho-semantic scales is observed on the axis of the «Preservation» bloc (conservatism) in relation to the individual value of «Self-direction». In addition, the specificity of the interconnection between the assessments of the subjectivity the volunteer community and sources of meaningfulness were found out. Namely, their combined influence on the assessment of the significance of value-motivational tendencies is observed.Conclusion. In general, the obtained data allow us to conclude that there is a holistic basis, which manifests itself in the conditioning the specifics of the interconnection of different subject areas of assessment. These areas of assessment act as complementary in the psycho-semantic representation of the construction of collective subjectivity by the subject of mental self-organization. The identified holistic basis also allows substantiating the assumptions about the existence of the criterion of assignment of significance as a singular semantic object in the structure of subjective experience. In turn, with criterion of assignment of significance is associated realization of the semantic function of the personality in the representation of collective subjectivity within the subjective experience.
Keywords: collective subjectivity, psycho-semantic model, subjective experience, subject of self-organization, forms of psyche.